A biodegradable, microstructured, electroconductive and nano-integrated drug eluting patch (MENDEP) for myocardial tissue engineering - Caterina Cristallini; Daniela Rossin; Roberto Vanni; Niccoletta Barbani; Chiara Bulgheresi; Massimiliano Labardi; Sadia Perveen; Silvia Burchielli; Domiziana Terlizzi; Claudia Kusmic; Silvia Del Ry; Manuela Cabiati; et al. (Bioactive Materials)
We produced a microstructured, electroconductive and nano-functionalized drug eluting cardiac patch (MENDEP) designed to attract endogenous precursor cells, favor their differentiation and counteract adverse ventricular remodeling in situ. MENDEP showed mechanical anisotropy and biaxial strength comparable to porcine myocardium, reduced impedance, controlled biodegradability, molecular recognition ability and controlled drug release activity. In vitro, cytocompatibility and cardioinductivity were demonstrated. Migration tests showed the chemoattractive capacity of the patches and conductivity assays showed unaltered cell-cell interactions and cell beating synchronicity. MENDEP was then epicardially implanted in a rat model of ischemia/reperfusion (I/R). Histological, immunofluorescence and biomarker analysis indicated that implantation did not cause damage to the healthy myocardium. After I/R, MENDEP recruited precursor cells into the damaged myocardium and triggered their differentiation towards the vascular lineage. Under the patch, the myocardial tissue appeared well preserved and cardiac gap junctions were correctly distributed at the level of the intercalated discs. The fibrotic area measured in the I/R group was partially reduced in the patch group.Overall, these results demonstrate that MENDEP was fully retained on the epicardial surface of the left ventricle over 4-week implantation period, underwent progressive vascularization, did not perturb the healthy myocardium and showed great potential in repairing the infarcted area.